2022
DOI: 10.1186/s12885-021-09096-6
|View full text |Cite
|
Sign up to set email alerts
|

The Patient Navigator: Can a systematically developed online health information tool improve patient participation and outcomes related to the consultation in older patients newly diagnosed with colorectal cancer?

Abstract: Background Older cancer patients may search for health information online to prepare for their consultations. However, seeking information online can have negative effects, for instance increased anxiety due to finding incorrect or unclear information. In addition, existing online cancer information is not necessarily adapted to the needs of older patients, even though cancer is a disease often found in older individuals. Objective The aim of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 65 publications
0
9
0
Order By: Relevance
“…Across these studies, five reported using technology other than email or telephone calls. This included Google Hangouts and WhatsApp, 95 an online patient navigation tool, 96 social media and phone applications, 97 Zoom, 98 and web‐based tool and video conferencing 99 . Four implementation and feasibility studies were also included 95,100–102 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Across these studies, five reported using technology other than email or telephone calls. This included Google Hangouts and WhatsApp, 95 an online patient navigation tool, 96 social media and phone applications, 97 Zoom, 98 and web‐based tool and video conferencing 99 . Four implementation and feasibility studies were also included 95,100–102 .…”
Section: Resultsmentioning
confidence: 99%
“…One study found that using caregiver navigators in combination with web‐based tools could connect participants to existing social support services, resulting in valued discussions with patients 99 . Another study indicated that using an online patient navigator tool to complement the information provided during a consultation with a health care provider resulted in increased patient satisfaction, with lower reported anxiety levels 96 . Finally, a study on navigation delivered by telemedicine (with the mode of delivery depending on patient preference) was identified as feasible and useful in a resource‐limited setting 95 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, another recent study has provided older patients with colorectal cancer with a self-tailored online health information tool to navigate treatment options and has reported improved patient participation and decreased anxiety following consultation. 6 By providing engaging online platforms that complement consultation with providers, such decision aids provide patients with an opportunity for interactive and durable knowledge building to make well-considered medical decisions. These can serve as models for existing online medical information on CRS and HIPEC to follow.…”
Section: Improving Online Resources For Cytoreductive Surgery and Hip...mentioning
confidence: 99%